Mindfulness and Counsellor Self-Efficacy among Pre-Service Counsellors in a South-Western Nigerian Tertiary Institution - Agokei, Roland Chukwudi (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2025)
This study examined the correlates between mindfulness and counselling self-efficacy among the pre-service counsellors. The study used a total sample of 200 final year students in the Department of Educational Foundations and Counselling Adeyemi Federal University of Education, Ondo, Nigeria. Two standardized and validated scales were used for the collection of data (mindfulness scale, r = 0.71; counsellor activity self-efficacy scale, r = 0.72). Three research hypotheses were raised and answered at 0.05 level of significance. The findings indicates that: a significant correlation was found in the mindfulness and counselling self-efficacy of the participants, significant difference also exists in the levels of mindfulness and counselling self-efficacy of the participants, with high mindfulness performing better than the moderate and the low mindfulness. Results further reveals the participants mindfulness was the same irrespective of their gender. Implications of mindfulness on counselling self-efficacy of students at all levels generally and some effective ways of promoting of mindfulness were suggested.